2019
DOI: 10.4491/eer.2019.387
|View full text |Cite
|
Sign up to set email alerts
|

Cathodic reduction characteristics of 2-chloro-4-nitrophenol in microbial electrolysis cell

Abstract: Microbial electrolysis cell (MEC) has been constructed to study the degradation characters of 2-chloro-4-nitrophenol (2C4NP) in waste water. The effects of applied voltage, initial concentration of substrate and co-matrix species on the reduction and degradation of 2C4NP were studied. Qualitative and quantitative analysis of 2C4NP residues and degradation intermediate by using UV-Vis, HPLC, HPLC/MS/MS, IC and other analytical testing techniques. The degradation mechanism of 2C4NP in MEC cathode was proposed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…EPS production, chemotactic processes, and cell migration play an important role during the degradation of organic pollutants or purification. It is found that gene modification of QS may assist in creating designed biofilms with enhanced degradation kinetic models and increase the performance of MFCs [84]. Moreover, a rhamnolipid synthesis which QS controls contributes to biofilm design by maintaining open biofilm water channels during matrix growth [85].…”
Section: Quorum Sensingmentioning
confidence: 99%
“…EPS production, chemotactic processes, and cell migration play an important role during the degradation of organic pollutants or purification. It is found that gene modification of QS may assist in creating designed biofilms with enhanced degradation kinetic models and increase the performance of MFCs [84]. Moreover, a rhamnolipid synthesis which QS controls contributes to biofilm design by maintaining open biofilm water channels during matrix growth [85].…”
Section: Quorum Sensingmentioning
confidence: 99%
“…Therefore, the purpose of this study was to evaluate the reproducibility of using different counter electrodes for anode and cathode LSV tests in a microbial electrolysis cell (MEC). The anode and cathode used in the experiment were carbon fiber brush and stainless steel mesh commonly used in MECs [60,61]. To compare reproducibility, the counter electrodes used in this study were Pt wire, stainless steel wire, and mesh in anode LSV tests.…”
Section: Introductionmentioning
confidence: 99%